Perancangan Sistem Kontrol dan Monitoring pada Robot Sadetec Berbasis IoT - Damiri, Adam; Saragih, Yuliarman; Latifa, Ulinnuha (Jurnal Teknologi Elekterika, 2022)
In the era of advanced technology, technology helps various fields of industrial work, agriculture, education, and other fields. Work such as supervising the queue of visitors or counters by utilizing technology can minimize the spread of the Covid-19 virus. Robot Line Follower technology monitors the distance of the visitor queue or counter can minimize the spread of the Covid-19 virus, and its minimalist form is easy for use and storage. Sadistic Robot (Smart Detection Distance for Queue) uses Line Follower technology plus the use Internet and smartphones that can be used by anyone and anywhere, thus monitoring or supervising the queue to maintain a safe distance so as not to be infected with the Covid-19 virus. This research is to create a control and monitoring system to monitor the distance of the queue of visitors or counters using the Internet of Things system or wifi internet network. Utilization in this study using a blynk application found on smartphones. Based on the test results, NodeMCU can connect to the Internet within 10 meters of the internet source. Then, the control system can receive commands from applications with a delay of less than 1 second, and the Blynk application monitoring system can receive sensor data in real-time in conditions of 10 meters.